Active short-circuit capacity identification method for LCC-HVDC system considering the integration of renewable energy - Peng, Maolan; He, Xiaopeng; Xiao, Jiachen; Feng, Lei; Liao, Fangqun; Jiang, Wen (Frontiers in Electronics, 2025)
For LCC-HVDC system with renewable energy integration, the randomness and variability of renewable energy will cause wide variations in the short-circuit capacity provided by the AC system. To effectively assess the supporting capability of the AC system, this paper proposes an active short-circuit capacity identification method for LCC-HVDC system considering the integration of renewable energy. First, an equivalent AC system was established based on Thevenin theorem, and the equivalent electromotive force was calculated. Then, the sensitivity of the voltage at the point of common coupling (PCC) to the active and reactive power flowing through the PCC was computed. Through sensitivity analysis, the key factors affecting the identification of the equivalent resistance and reactance were studied. Based on this, an active short-circuit capacity identification method combining the switching of filters and changes in DC power was proposed. Finally, a simulation model of LCC-HVDC system with grid-following wind power integration was built in PSCAD/EMTDC for verification. The results show that the proposed method is applicable to AC systems with different impedance characteristics. Moreover, with the increase of the grid-following renewable energy, the short-circuit capacity provided by the AC system shows a decreasing trend. The proposed method can actively identify the short-circuit capacity of AC system with renewable energy, thus provides a theoretical basis for the development of control strategies for LCC converter station under different AC system strength.